Estimating matching games with transfers - Jeremy T. Fox (Centre for Microdata Methods and Practice (cemmap), 2016)
I explore the estimation of transferable utility matching games, encompassing many-to-many matching, marriage and matching with trading networks (trades). I introduce a matching maximum score estimator that does not suffer from a computational curse of dimensionality in the number of agents in a matching market. I apply the estimator to data on the car parts supplied by automotive suppliers to estimate the returns from different portfolios of parts to suppliers and automotive assemblers.
Keywords: 330